If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24x + -40 = 20x + -40 Reorder the terms: -40 + 24x = 20x + -40 Reorder the terms: -40 + 24x = -40 + 20x Add '40' to each side of the equation. -40 + 40 + 24x = -40 + 40 + 20x Combine like terms: -40 + 40 = 0 0 + 24x = -40 + 40 + 20x 24x = -40 + 40 + 20x Combine like terms: -40 + 40 = 0 24x = 0 + 20x 24x = 20x Solving 24x = 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 24x + -20x = 20x + -20x Combine like terms: 24x + -20x = 4x 4x = 20x + -20x Combine like terms: 20x + -20x = 0 4x = 0 Divide each side by '4'. x = 0 Simplifying x = 0
| 8/2s^-3 | | 135=16x^2+110x+5 | | (3a-6g)(3a+5g)=0 | | x+2y=18.5 | | 8x-4.25=86 | | 5(2-6n)=70 | | 2(x+14)+(2x+-14)= | | -6n=24-14n | | 3+6y=4+8y | | 35x-5y=2.7 | | 2.333333333333333333333333333333333333333333y=84 | | X(x^2+7x)=-60 | | 3q^2-6q=2q^2-8q+63 | | 3t/5=5 | | 7(x-1)=3x+13 | | 3x-5y=2.5 | | 2k^2-13k-24= | | 3.2/8 | | y=9(1)+3 | | x+100=43 | | 3x^2/y | | 6=x/(3-x) | | 6x^2-8y=-3 | | x=-16y^2+64y+30 | | (8e^2+5e+1)-(8e^2+5)=8e+7 | | (-3)/(6) | | 9x-7=5x+25 | | 0.167=(x)/(0.1497-x) | | x*20=4 | | 2x+7x-12+4x+4x+2+5x=540 | | 7x=21-2x | | 4x-13=2x+3y |